Nanometer flaky magnesium pyrophosphate composite aerogel and preparation method thereof
By preparing nanosheet magnesium pyrophosphate composite aerogels, combined with the porous network structure of silica aerogels, the problem of existing radiation refrigeration materials that easily turn yellow and degrade under environmental conditions is solved, and efficient radiation is achieved. cooling and thermal insulation effects, and maintains the stability of the material.
Patent Information
- Application Number
- CN202411468647.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
Smart Images

Figure CN119349527A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new materials and relates to radiation refrigeration materials, and in particular to a nano-flaky magnesium pyrophosphate composite aerogel and a preparation method thereof. Background Art
[0002] With the development of social economy and the acceleration of industrialization, global energy consumption is increasing day by day, and air conditioning in buildings accounts for a considerable proportion of electricity consumption. It is expected that by 2050, the demand for cooling will triple. Therefore, it is particularly important to develop new energy-saving materials to reduce the pressure on the power grid and combat global warming.
[0003] Passive daytime radiative cooling technology is a method of reducing energy demand by applying radiative cooling materials to building envelopes. These radiative cooling materials can reflect more than 90% of solar radiation and emit heat directly into the cold outer space in the form of long-wave infrared light (LWIR) through the atmospheric transparent window (8-13 μm) to achieve a temperature below ambient. The radiative cooling materials have high reflectivity in the visible to near-infrared band and high emissivity in the atmospheric transparent window (8-13 μm). Although a variety of methods have been proposed, such as polymer-metal hybrid films, porous polymer coatings and foams, polymer-dielectric coatings, delignified wood, and multilayer polymer films, these organic polymers are not very effective under ambient conditions (including ultraviolet (UV) light, heat, water, and environmental chemicals such as NO x 、SO x and O3) tend to yellow and degrade over time, leading to increased solar absorption of the material, which reduces cooling effectiveness and can even produce a heating effect.
[0004] Therefore, developing a radiation cooling material that has both high solar reflectivity and high infrared emissivity and can maintain stability under different environmental conditions is a technical problem that needs to be urgently solved by technical personnel in this field. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a nano-flaky magnesium pyrophosphate composite aerogel and a preparation method thereof. The nano-flaky magnesium pyrophosphate composite aerogel prepared by the present invention has high solar reflectivity and high infrared emissivity, and also has good stability.
[0006] The technical solution of the present invention is achieved in this way: A method for preparing a nano-flaky magnesium pyrophosphate composite aerogel is characterized by comprising the following steps: (1) Magnesium chloride, sodium pyrophosphate and water are mixed and the pH is adjusted to 4-6, and then transferred to a reactor for hydrothermal reaction. After the reaction is completed, the mixture is filtered, washed and dried, and then placed in a muffle furnace for reaction at 500-900°C for 2-4 hours. After cooling to room temperature, magnesium pyrophosphate is obtained; (2) mixing ethanol, water and tetraethyl orthosilicate to obtain a mixed solution A, then adding the magnesium pyrophosphate obtained in step (1) to the mixed solution A, mixing well and adjusting the pH to 2-3, stirring and reacting for 2-4 h, then adjusting the pH to 7-8 and placing in a 40-50° C. water bath for 10-30 min; (3) After standing, the reaction product is added to a 50% by mass ethanol solution, aged at 40-50°C for 24-48 hours, and then subjected to multi-step solvent replacement with an organic solvent. A modifier is then used for hydrophobic modification, and then the organic solvent is removed by washing and soaking for multiple times. Finally, the composite aerogel is obtained by freeze-drying.
[0007] Furthermore, in step (1), the molar mass ratio of magnesium chloride to sodium pyrophosphate is 2:1-2.
[0008] Furthermore, in step (1), the hydrothermal reaction is carried out at 150-180°C for 24-30 h.
[0009] Furthermore, in step (1), the temperature during the reaction in the muffle furnace is 500°C.
[0010] Furthermore, in step (2), the molar mass ratio of ethanol, water and tetraethyl orthosilicate in the mixed solution A is 8:4:1-2.
[0011] Furthermore, in step (2), the mass of magnesium pyrophosphate added per 50 g of mixed solution A is 0.1-0.3 g.
[0012] Furthermore, in step (3), the specific steps of the multi-step solvent replacement are: first, replace with a 100% ethanol solution by mass, then replace with a mixed solution of 50% ethanol by mass and 50% n-hexane by mass, and finally replace with a 100% n-hexane solution by mass, and the time for each replacement step is 8-16 hours.
[0013] Furthermore, in step (3), the modifier is one of trimethylchlorosilane and octadecyltrichlorosilane, and the volume ratio of the modifier to the mixed solution A is 1:9-10; after the modification, a 99% by mass n-hexane solution is used for washing and soaking to remove the organic solvent.
[0014] Furthermore, in step (3), during freeze drying, the product is first pre-cooled at -18°C for 8-12 h, and then placed in a freeze drying device at -60°C for vacuum freeze drying for 24 h.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The magnesium pyrophosphate prepared by the present invention has a nano-flaky structure. After being compounded with the silica aerogel, the aerogel is evenly distributed on the surface of the nano-flaky magnesium pyrophosphate. The magnesium pyrophosphate has high reflectivity and high emissivity, and can effectively reduce the temperature of the surface of the building. Compared with the blocky magnesium pyrophosphate, the magnesium pyrophosphate with a nano-flaky structure has good Rayleigh scattering performance, which can effectively avoid heat reflection and emission to the surrounding environment, ensure that the heat is directly emitted to the outer space, further improve the radiation cooling effect, and reduce the temperature of the surface of the building; and the silica aerogel distributed on the surface of the magnesium pyrophosphate has a porous network structure, the gas dispersed in the pores of the SiO2 aerogel is mainly N2 and O2, the mean free path of the movement of gas molecules is greater than the pore size of the SiO2 aerogel, the collision probability of gas molecules is almost zero, the heat transfer by convection is very low, the gas phase thermal conductivity is extremely small, and a large number of pores form countless interfaces for reflection, refraction, and absorption of thermal radiation, which can greatly inhibit the heat loss caused by thermal radiation, and has good thermal insulation performance, thereby further effectively reducing the surface temperature of the building.
[0016] 2. The composite aerogel prepared by the present invention uses PekinElmer Lambda750S, and polytetrafluoroethylene is selected as the reference for the backing, and the solar reflectivity is measured to be 94%, and the emissivity is measured by Fourier infrared spectroscopy (FTIR with GoldenGate ATR) with a gold integrating sphere to be 91%. The excellent radiation cooling and heat insulation capabilities can make the surface of the composite aerogel about 7°C lower than the ambient temperature.
[0017] 3. The composite aerogel prepared by the present invention is an inorganic composite material with good stability and hydrophobicity. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 -Actual photo of the composite aerogel prepared in Example 1.
[0019] Figure 2 -EDS spectrum of the composite aerogel prepared in Example 1.
[0020] Figure 3 -SEM image of magnesium pyrophosphate prepared in Example 1.
[0021] Figure 4 -TEM image of the composite aerogel prepared in Example 1.
[0022] Figure 5-Contact angle diagram of the composite aerogel prepared in Example 1.
[0023] Figure 6 -Reflectivity diagram of the composite aerogel prepared in Example 1 within the solar spectrum.
[0024] Figure 7 -Emissivity diagram of the composite aerogel prepared in Example 1 in the 2.5-20 μm atmospheric transparent window.
[0025] Figure 8 -Schematic diagram of the temperature test structure.
[0026] Fig. 9 - Example 1 Temperature versus time curve.
[0027] Fig.10 SEM images of magnesium pyrophosphate obtained in Examples 1-3 and Comparative Examples 1-3.
[0028] Fig.11 -Reflection graphs of magnesium pyrophosphate obtained in Examples 1-3 and Comparative Examples 1-3.
[0029] Fig.12 -Emission diagrams of magnesium pyrophosphate obtained in Examples 1-3 and Comparative Examples 1-3.
[0030] Fig.13 -SEM images of the composite aerogels prepared in Example 1, Example 4, Example 5 and Comparative Example 4. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0032] Example 1 (1) Preparation of magnesium pyrophosphate: Take 3.8 g of magnesium chloride and 5.3 g of sodium pyrophosphate, add 60 ml of deionized water, stir for 2 h, adjust the pH to 4 (when adjusting the pH value, use hydrochloric acid and ammonia water), then transfer it to a hydrothermal reactor, keep it at 180 °C for 24 h, filter it, and then wash it three times with deionized water and ethanol respectively to obtain a white powder. Then put the white powder into a drying oven and dry it at 80 °C for 24 h, then put it into a high-temperature muffle furnace and keep it at 500 °C for 2 h, and cool it to room temperature to obtain magnesium pyrophosphate (Mg2P2O7) powder.
[0033] (2) Preparation of composite aerogel: Take drugs according to the molar mass ratio of tetraethyl orthosilicate: deionized water: anhydrous ethanol = 1:4:8, then mix and stir to obtain 90 mL of mixed solution (a total of 50 g), then weigh 0.2 g of Mg2P2O7 powder and add it to the above mixed solution. After stirring for a few minutes, adjust the pH of the solution to 3 with concentrated hydrochloric acid and stir for 2 h. Then add ammonia water to adjust the pH to 8 and place it in a 50 ℃ water bath. When it does not flow when tilted at 45° in the beaker, it forms a gel. Then add 50% ethanol aqueous solution to the obtained gel and age it for 24 h. Then, perform solvent replacement by a multi-step solvent replacement method (the specific steps of solvent replacement are: the first step is to use 100% ethanol solution for replacement, the second step is to use a mixed solution of 50% ethanol solution and 50% n-hexane solution for replacement, and the third step is to use 100% n-hexane solution for replacement. The three steps are replaced for 12 h respectively). Then, 9 mL of trimethylchlorosilane (TMCS) solution was used as a modifier to hydrophobically modify the gel. After the modification, the modified gel surface was washed and soaked several times with 99% n-hexane solution to remove the residual organic solvent on the gel surface. After the replacement was completed, it was precooled at -18 °C for 12 h, and then placed in a freeze-drying device precooled to -60 °C for vacuum freeze-drying for 24 h to obtain Mg2P2O7 / SiO2 composite aerogel.
[0034] Example 2 This example is the same as Example 1, except that in step (1) of this example, the pH is adjusted to 5.
[0035] Example 3 This example is the same as Example 1, except that in step (1) of this example, the pH is adjusted to 6.
[0036] Example 4 This embodiment is the same as embodiment 1, except that in step (2) of this embodiment, the amount of Mg2P2O7 powder added is 0.1 g.
[0037] Example 5 This embodiment is the same as embodiment 1, except that in step (2) of this embodiment, the amount of Mg2P2O7 powder added is 0.3 g.
[0038] Comparative Example 1 This example is the same as Example 1, except that in step (1) of this example, the pH is adjusted to 8.
[0039] Comparative Example 2 This example is the same as Example 1, except that in step (1) of this example, the pH is adjusted to 9.
[0040] Comparative Example 3 This example is the same as Example 1, except that in step (1) of this example, the pH is adjusted to 10.
[0041] Comparative Example 4 This embodiment is the same as embodiment 1, except that in step (2) of this embodiment, the amount of Mg2P2O7 powder added is 0.4 g.
[0042] 1. The actual photo of the composite aerogel prepared in this embodiment is as follows Figure 1 As shown in the figure, the composite aerogel is a white solid. The composite aerogel is subjected to energy spectrum analysis, and the obtained EDS spectrum is as follows Figure 2 As shown in the figure, it can be seen that the prepared composite aerogel is Mg2P2O7 / SiO2 composite aerogel, and each element is evenly distributed.
[0043] 2. The SEM image of magnesium pyrophosphate obtained in this embodiment is as follows: Figure 3 As can be seen from the figure, magnesium pyrophosphate has a nano-sheet structure, has good Rayleigh scattering performance, and can effectively increase the contact area with the incident light, which is beneficial to improve the reflectivity.
[0044] 3. The TEM image of the composite aerogel prepared in this embodiment is as follows: Figure 4 As shown in the figure, magnesium pyrophosphate is mixed in the silica aerogel. The contact angle diagram of the composite aerogel prepared in this embodiment is as follows: Figure 5 As shown in the figure, it can be seen that the contact angle of the Mg2P2O7 / SiO2 composite aerogel prepared by the present invention is 135°, and it has good hydrophobicity.
[0045] 4. The reflectivity of the composite aerogel prepared in this embodiment was tested using a PekinElmer Lambda750S, using polytetrafluoroethylene as a reference, a xenon lamp and an iodine tungsten lamp as light sources, and a test wavelength range of 0.3 μm-2.5 μm with an interval of 0.002 μm. The reflectivity of the composite aerogel prepared in this embodiment within the solar spectrum range is shown in the figure below: Figure 6 As shown in the figure: it can be seen that its average reflectivity can reach 94% (AM1.5 solar spectrum as a reference).
[0046] The composite aerogel prepared in this embodiment was tested using a Fourier transform infrared spectrometer (FTIR with Golden Gate ATR) with a test wavelength range of 2.5 μm-20 μm and an interval of 0.005 μm. The emissivity of the composite aerogel prepared in this embodiment in the 2.5-20 μm atmospheric transparent window is shown in FIG. Figure 7As shown, it can be seen from the figure: it can be seen that the average emissivity in the atmospheric window band (8-13 μm) is 91% (black body energy distribution is used as a reference).
[0047] See also Figure 7 Aluminum foil is horizontally placed in a foam box with an aluminum foil outer surface, and the composite aerogel described in this embodiment is coated on the upper surface of the aluminum foil. Then, the aluminum foil is placed on the roof and a temperature test is performed using a multi-temperature circuit thermometer. The multi-temperature circuit thermometer has four temperature probes, which respectively test the environment 1, the coating surface 2, the coating back 3, and the box aluminum foil 4. The measured temperature change curve over time is shown in FIG. Fig. 9 As shown in the figure, it can be seen that the measured temperature of the coating surface is on average about 6°C lower than the ambient temperature, indicating that the composite aerogel of the present invention has a good passive cooling effect.
[0048] 5. The SEM images of magnesium pyrophosphate (Mg2P2O7 powder) obtained in Examples 1-3 and Comparative Examples 1-3 are as follows: Fig.10 As shown, and correspond to Fig.10 (a) Fig.10 (b) Fig.10 (c) Fig.10 (d) Fig.10 (e) and Fig.10 (f) As can be seen from the figure, as the pH increases, the flake size also increases.
[0049] At the same time, the reflectivity graph and emissivity graph of magnesium pyrophosphate (Mg2P2O7 powder) obtained in Examples 1-3 and Comparative Examples 1-3 are as follows: Fig.11 and Fig.12 As shown in the figure, the magnesium pyrophosphate prepared by the present invention can reflect more than 90% of sunlight, and the emissivity in the atmospheric transparent window (8-13 μm) is more than 90%. It can also be found that within the pH range of 4 to 10, the emissivity and reflectivity of magnesium pyrophosphate decrease as the pH increases.
[0050] 6. The SEM images of the composite aerogels prepared in Example 1, Example 4, Example 5 and Comparative Example 4 are as follows: Fig.13 As shown in the figure, it can be seen that with the increase of the addition amount of magnesium pyrophosphate (Mg2P2O7 powder), the microstructure of the composite aerogel gradually changes from a network structure to a network-sheet inclusion structure and a network-block inclusion structure.
[0051] Finally, it should be noted that the above embodiments of the present invention are only examples for illustrating the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes and modifications can be made based on the above description. It is impossible to list all implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A method for preparing a nano-flaky magnesium pyrophosphate composite aerogel, characterized in that: The specific steps include: (1) Magnesium chloride, sodium pyrophosphate and water are mixed and the pH is adjusted to 4-6, and then transferred to a reactor for hydrothermal reaction. After the reaction is completed, the mixture is filtered, washed and dried, and then placed in a muffle furnace for reaction at 500-900°C for 2-4 hours. After cooling to room temperature, magnesium pyrophosphate is obtained; (2) mixing ethanol, water and tetraethyl orthosilicate to obtain a mixed solution A, then adding the magnesium pyrophosphate obtained in step (1) to the mixed solution A, mixing well and adjusting the pH to 2-3, stirring and reacting for 2-4 h, then adjusting the pH to 7-8 and placing in a 40-50 ° C water bath for 10-30 min; (3) After standing, the reaction product is added to a 50% by mass ethanol solution, aged at 40-50°C for 24-48 hours, and then subjected to multi-step solvent replacement with an organic solvent. A modifier is then used for hydrophobic modification, and then the organic solvent is removed by washing and soaking for multiple times. Finally, the composite aerogel is obtained by freeze-drying.
2. The method for preparing a nano-flaky magnesium pyrophosphate composite aerogel according to claim 1, characterized in that: In step (1), the molar mass ratio of magnesium chloride to sodium pyrophosphate is 2:1-2.
3. The method for preparing a nano-flaky magnesium pyrophosphate composite aerogel according to claim 1, characterized in that: In step (1), the hydrothermal reaction is carried out at 150-180°C for 24-30 hours.
4. The method for preparing a nano-flaky magnesium pyrophosphate composite aerogel according to claim 1, characterized in that: In step (1), the temperature during the reaction in the muffle furnace is 500°C.
5. The method for preparing a nano-flaky magnesium pyrophosphate composite aerogel according to claim 1, characterized in that: In step (2), the molar mass ratio of ethanol, water and tetraethyl orthosilicate in the mixed solution A is 8:4:1-2.
6. The method for preparing a nano-flaky magnesium pyrophosphate composite aerogel according to claim 1 or 5, characterized in that: In step (2), the mass of magnesium pyrophosphate added per 50 g of mixed solution A is 0.1-0.3 g.
7. The method for preparing a nano-flaky magnesium pyrophosphate composite aerogel according to claim 1, characterized in that: In step (3), the specific steps of the multi-step solvent replacement are: first, replace with a 100% ethanol solution by mass, then replace with a mixed solution of 50% ethanol by mass and 50% n-hexane by mass, and finally replace with a 100% n-hexane solution by mass. The time for each replacement step is 8-16 hours.
8. The method for preparing a nano-flaky magnesium pyrophosphate composite aerogel according to claim 1, characterized in that: In step (3), the modifier is one of trimethylchlorosilane and octadecyltrichlorosilane, and the volume ratio of the modifier to the mixed solution A is 1:9-10; after the modification, a 99% by mass n-hexane solution is used for washing and soaking to remove the organic solvent.
9. The method for preparing a nano-flaky magnesium pyrophosphate composite aerogel according to claim 1, characterized in that: In step (3), during freeze drying, the product is first pre-cooled at -18 °C for 8-12 h, and then placed in a freeze drying device at -60 °C for vacuum freeze drying for 24 h.
10. A nano-sheet magnesium pyrophosphate composite aerogel, characterized in that: The nano-sheet magnesium pyrophosphate composite aerogel is prepared by the preparation method of any one of claims 1 to 9.